The Persistence of Desire: Gay Men Online and Queer Visuality - Barbosa Gadelha, Kaciano (Arte y Políticas de Identidad, 2017)
Queer forms of sociality online have been established as a research field for many social studies that contributed to our contemporary comprehension of new geographies of sexualities. Such a task required a cautious review of existent methodologies and conceptual tools, especially when sexuality comes up as an axis of investigation. In this paper I explore the persistence of the category of “desire” for the study of dissident sexualities online. Although a critical approach to desire is present in queer scholarship, my argument relies on implementing theoretical queer and/or feminist formulations of desire. It has been a problematic standard to combine theories on queer desire without reflecting about the field in which such theories may be applied. Desire as a category has also to do with the dismantling of cruising geographies and with the errant aspect inherent to cruising practices. This paper, by discussing theoretically the relationship between “desire”, “visualization”, and the “digital” points out the disruptive aspect of desire in relation to online ways of seeing and performativity.